РУМИ МАСНАВИІНДЕГІ АДАМНЫҢ ӨЗІН-ӨЗІ ТАНУ ІЛІМІ (Journal of Oriental Studies, 2016)
В статье рассматриваются поэтические особеннос-ти иранского поэта Моулави и его глубокие размыш-ления о человеке и бытие. Проблемы религии и Богазанимают особое место в творчестве поэта. Решениемногих нравственных проблем Моулави связывает слюбовью к Богу, Создателю.The article deals with the poetic features of the Iranianpoet, Moulavi, and his deep thoughts about a human beingand a life. In his works the poet focuses on religion andGod aspects. Moulavi sees the solutions of many moralissues in the the love of God, the Creator.